The evolution of morphological development is congruent with the species phylogeny in the genus Streptomyces - Wang, Min; Li, Cong-Jian; Zhang, Zhen; Li, Pan-Pan; Yang, Ling-Ling; Zhi, Xiao-Yang (Frontiers in Microbiology, 2023)
As the canonical model organism to dissect bacterial morphological development, Streptomyces species has attracted much attention from the microbiological society. However, the evolution of development-related genes in Streptomyces remains elusive. Here, we evaluated the distribution of development-related genes, thus indicating that the majority of these genes were ubiquitous in Streptomyces genomes. Furthermore, the phylogenetic topologies of related strict orthologous genes were compared to the species tree of Streptomyces from both concatenation and single-gene tree analyses. Meanwhile, the reconciled gene tree and normalization based on the number of parsimony-informative sites were also employed to reduce the impact of phylogenetic conflicts, which was induced by uncertainty in single-gene tree inference based merely on the sequence and the bias in the amount of phylogenetic information caused by variable numbers of parsimony-informative sites. We found that the development-related genes had higher congruence to the species tree than other strict orthologous genes. Considering that the development-related genes could also be tracked back to the common ancestor of Streptomyces, these results suggest that morphological development follows the same pattern as species divergence.